Comparison of resuspended road dust concentration for identifying optimum sampling position on a mobile laboratory vehicle. Issue 11 (2nd November 2021) - Noh, Seung-Yoon; Lee, Kyung-Ran; Noh, Jung-Hun; Kim, Hyung-Seok; Yook, Se-Jin
Abstract: The accurate measurement of resuspended road dust from driving vehicles is key to assessing its role in air pollution. In this study, we used numerical analysis to investigate the behavior of resuspended road dust and selected the optimum sampling positions for use in a mobile laboratory (ML) to measure resuspended road dust emissions. Transient simulation of vehicle driving was performed by depicting wheel rim shape and tire tread pattern in detail. The resuspended road dust distributions generated around the vehicle wheels and the flow around the vehicle were analyzed according to the vehicle speed. Based on the analysis, four sampling positions with concentrated distributions of resuspended road dust were selected. To verify the simulation results, sampling inlets were installed on a ML in the selected positions, and resuspended road dust was collected at each position using a Teflon filter at vehicle speeds of 30, 40, and 50 km/h. Mass measurements of the resuspended road dust collected at the four locations showed that the most dust was collected at the position at the bottom of the vehicle immediately behind the wheel, and the overall trend was similar to the simulation results. Therefore, when measuring resuspended road dust using a ML, sampling inlets installed at the locations derived in this study are expected to yield more effective measurements for representing the pollution level of the road. Copyright © 2021 American Association for Aerosol Research